2002
DOI: 10.1002/jmri.10174
|View full text |Cite
|
Sign up to set email alerts
|

Vascular‐targeted molecular imaging using functionalized polymerized vesicles

Abstract: In this review we will discuss the use of multivalent polymerized vesicles (PVs) combined with magnetic resonance imaging (MRI) and gamma scintigraphy to image expression of vascular molecular receptors in vivo. Specifically, we will present our data on the use of this technology to design imaging agents toward specific vascular receptors in both a mouse and rabbit tumor model and in the EAE mouse, a model for human multiple sclerosis (MS). Examples will be shown where the in vivo specificity of the targeted m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…The use of surface-functionalized nanoparticles provides an alternative means of increasing the sensitivity of detection, particularly in the case of molecular MRI contrast agents. A whole range of nanoparticles have been used including polymerized vesicles (from derivatised polymerizable lipids; Li & Bednarski 2002;Wickline & Lanza 2002), caged magnetic nanoparticles (Schellenberger et al 2004), nanoparticulate emulsions (Winter et al 2003). The functional groups attached were aimed at targeting biochemical epitopes (e.g.…”
Section: Targeting and Sensingmentioning
confidence: 99%
“…The use of surface-functionalized nanoparticles provides an alternative means of increasing the sensitivity of detection, particularly in the case of molecular MRI contrast agents. A whole range of nanoparticles have been used including polymerized vesicles (from derivatised polymerizable lipids; Li & Bednarski 2002;Wickline & Lanza 2002), caged magnetic nanoparticles (Schellenberger et al 2004), nanoparticulate emulsions (Winter et al 2003). The functional groups attached were aimed at targeting biochemical epitopes (e.g.…”
Section: Targeting and Sensingmentioning
confidence: 99%
“…These nanometer-sized particles have a large effect on MRI signal intensities due to the fact that they are superparamagnetic and disrupt magnetic field homogeneity to an extent much larger than their size. A growing number of studies have demonstrated the usefulness of USPIOs and MRI to detect receptors (3,(5)(6)(7)(8) and monitor cell migration (9)(10)(11). Indeed, when a cell is labeled with millions of USPIOs, single cells can be detected by MRI even though the MRI is acquired at low resolution (50-100 m) compared with the size of the cells (5-20 m; refs.…”
mentioning
confidence: 99%
“…gadolinium). Since the magnitude of the relaxation by a single paramagnetic label is generally too small, functionalized polymerized vesicles or nanoparticles are additionally needed to attach more than one label in each molecular imaging probe [8]. In US, sensing is accomplished through conjugation of disease-specific ligands for the targeted molecule to a microbubble surface or other acoustically active nanoparticles.…”
Section: Imaging Probesmentioning
confidence: 99%